Human-Leopard Conflict in Girimukti Village, Sukabumi, Indonesia - RUHYAT PARTASASMITA; SYA SYA SHANIDA; JOHAN ISKANDAR; ERRI NOVIAR MEGANTARA; TEGUH HUSODO; PARIKESIT PARIKESIT; NICHOLAS MALONE (Society for Indonesian Biodiversity, 2016)
Partasasmita R, Shanida SS, Iskandar J, Megantara EN, Husodo T, Malone N. 2016. Human-Leopard Conflict in Girimukti Village, Sukabumi, Indonesia. Biodiversitas 17: 783-790. Populations of leopards continue to decrease over time. This decline is caused by many factors, such as decreasing animal prey and habitat loss. Due to a lack of animal prey, leopards frequently enter villages to find food, including livestock. Therefore, some conflicts between human-leopard have frequently occurred, and in many cases the leopard has been hunted by the villager. Consequently, the abundance of leopard in some areas of West Java have decreased. The aim of this research is to investigate: (i) local knowledge of the Girimukti Village on morphological variation of leopard; (ii) conflict between leopard and the people of Girimukti Village based on local knowledge; (iii) local knowledge on the hunting of leopard; and (iv) utilization of leopard resulting from human-leopard conflict in Girimukti Village, Sukabumi, West Java, Indonesia. Mixed methods andfield observation were applied in this study. The result of this study shows that the village people of Girimukti recognize variations of leopard and their behavior; conflict between humans and leopard has increased; hunting leopard is been undertaken by both traps and shotgun; and leopard are used for various purposes, such as trading skin and other body parts, food, traditional medicines, and as amulets. Based on this study, it can be inferred that many drivers of environmental changes that impact faunal and floral communities are social in origin and strongly related with peoples’ activities. As a result, in addition to biological properties, the social, economic and political systems must be considered and integrated into the conservation program of Javan leopards. Keywords: Girimukti Village, human-leopard conflict, leopard